Chemical Synthesis of Conductive Poly(methoxyaniline) in Hydroxyethylidenediphosphonic Acid - Sankar, A.; Kumaravel, M.; Rameshkumar, S.; Vijayan, M. (Asian Journal of Chemistry, 2013)
The poly(orthomethoxyaniline)-hydroxyethylidenediphosphonic acid salt has been prepared by chemical polymerization method. It was characterized by UV-visible, infrared spectroscopy, thermogravimetric analysis and conductivity measurements. The solubility tests were also performed at room temperature for the doped and dedoped polymers in different solvents. The morphology of the polymer samples was studied by scanning electron microscopy monographs.